Meet the shrews - Parsley, Reed.; Fox, Sparky (New York : Green Tiger Press, 1991)
Johnny forms a blues band with three other shrews and the musical mammals play to ecstatic audiences all over the world.
5.5
3-6
Keywords: Bands (Music) -- Fiction; Shrews -- Fiction; Bands (Music) -- Fiction; Shrews -- Fiction